Synthetic antimicrobial agent and antimicrobial fabrics: progress and challenges - Norashikin, Mat Zain; Akindoyo, John Olabode; Beg, M. D. H. (IIUM, Malaysia, 2018)
Recently, there is a strengthening requirement for antimicrobial fabrics that are resistant to pathogens, offer greater hygiene, and are protective in an active lifestyle. Synthetic compounds have been applied to impart antimicrobial properties to the fabrics. In this paper, synthetic antimicrobial agents, namely quaternary ammonium compounds (QACs), polyhexamethylene biguanide (PHMB), triclosan, and N-halamine are discussed along with their mechanisms of action. Research has been done on synthetic antimicrobial treatment of fabrics; the tested microorganisms used to determine their efficiency and durability are summarized. It is also found that although synthetic antimicrobial agents have excellent strength to kill the microorganisms, some of these antimicrobial agents are harmful and have adverse effects on the environment, safety, and health. Identification of these problems will provide future challenges to overcome and improve the techniques used for antimicrobial treatment of the fabrics. Based on the infromation presented herein, it is recommended that subsequent studies should consider the use of antimicrobial agents that are either obtained from plant sources or from microorganisms. On the other hand, nanotechnlogy should be explored for production of antimicrobial agents in further studies based on its potential to facilitate the production of environmentally benign antimicrobial agents.